STARTUP AS A TOOL FOR REALIZING INNOVATIVE POTENTIAL - MITSENKO, Nataliia; MISHCHUK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to scientifically substantiate the theoretical and applied aspects of the development of startups in Ukraine based on the realization of  personal innovative potential in the conditions of neo-economy and changes in social and labor relations under the influence of Industry 4.0.The role of startup projects as tools for implementing innovative entrepreneurial ideas is substantiated. The need to spread the startup movement for the development of the country's economy on an innovative basis during the war and during the post-war recovery period as a component of the national innovation system, a driver of the country's investment attractiveness and competitiveness, and the basis for the formation of a national startup ecosystem is proven.The essential and criterion features of startups are summarized, emphasizing the importance of the innovative idea and the intellectual potential of team members. At the same time, a person should be considered as the primary source of innovative ideas, which can later be implemented in startup projects. The dependence of the startup team's efficiency on entrepreneurial abilities, communication skills and creative thinking, the ability to work in a team, readiness for leadership and responsibility are emphasized.A comparative analysis of the areas of activity in which startup projects are implemented in Ukraine and in leading countries of the startup movement has been conducted, which allows us to assert that there are prerequisites for creating startups in Ukraine, for realizing the personal innovative potential of Ukrainians in the context of digitalization and Industry 4.0.From the point of view of the priority of human values ​​and human resources in achieving the goals of innovative development, startup projects provide an opportunity for self-realization of a person's entrepreneurial potential and personal innovative potential.
Keywords: startup project; personal innovation potential; startup team; startup ecosystem; startup movement